Mycobacterium llatzerense Lung Infection in a Liver Transplant Recipient: Case Report and Review of the Literature. Issue 8 (13th June 2013) - Teixeira, L.; Avery, R. K.; Iseman, M.; Arrossi, A. V.; Harrington, S.; Stephens, K.; Winans, C. G.
Abstract: Nontuberculous mycobacteria are increasingly encountered pathogens in organ transplant recipients. We report the first case of human disease attributed to Mycobacterium llatzerense that occurred in a liver transplant recipient in the midwestern United States who developed pneumonia and describe the treatment of this patient. Abstract : The authors describe a case of sub‐acute pneumonia in a liver transplant recipient due to Mycobacterium llatzerense, a recently described aerobic, rapidly growing mycobacterium that responded to treatment with ciprofl oxacin, minocycline and azithromycin.